The Mental Condition of a Manipulative Personality Refelected in the Main Character in David Fincher’s Gone Girl (2014) - Muchammad Alyan Chafash Chafiidzul Umam; Latifah Dwi Ariyani (Metaphor, 2023)
This research aims to analyze Amy Dunne mental condition as a as a manipulative person in David Fincher’s Gone Girl.This research uses a qualitative descriptive method to analyze the film entitled "Gone Girl" directed by David Fincher’s as a research objective. Data collection methods include observing and reading, identifying, classifying, and selecting. The method of analyzing data is by displaying, explaining and interpreting. Data were analyzed using theory from Sigmund Freud. The mental condition of the main character as a manipulative person Amy Dunne in “David Fincher’s Gone Girl (2014) when mental condition of Amy knowing her husband’s affair, when she trapped her ex-boyfriend, Amy in facing her parents, when facing revenge to her husband, and mental condition of amy when readiness to commiting suicide. Then Amy Dunne becomes a manipulative person.